Identifying the Effect of the Van Hill Model on the Development of Reasoning Thinking Skills among Fifth Graders in Biology - Hamid, Safaa Ahmed (Journal of Tikrit University for Humanities, 2020)
The sample of the research was determined by the students of the fifth grade of biological sciences in the General Directorate of Salahuddin Education - Department of Education of Al-Dour, in the preparatory school for boys and Al-Qastal preparatory School for boys of the academic year 2016-2017. The study sample was consisted of (63) students who were selected from the research community and were divided into two groups. The first group was consisted of (32) students studied the subject matter of biology according to the Van Hill model. The second group included (31) students who studied the subject matter according to the classical method . The two research groups were rewarded with a number of variables that may affect the integrity of experimental design for research: intelligence, age and achievement scores in biology for the previous academic year (2015-2016), prenatal testing of parental reasoning and educational level as well as some other internal safety measures The researcher himself taught the two groups. The search required the existence of a means which is the test of reasoning. The researcher prepared a test to measure explanatory thinking by (24) paragraphs (induction, synthesis & conclusion ), (8) paragraphs for each skill.